Cover Picture: Tuning Ground States of Bis(triarylamine) Dications: From a Closed‐Shell Singlet to a Diradicaloid with an Excited Triplet State (Angew. Chem. Int. Ed. 11/2014). Issue 11 (19th February 2014) - Su, Yuanting; Wang, Xingyong; Zheng, Xin; Zhang, Zaichao; Song, You; Sui, Yunxia; Li, Yizhi; Wang, Xinping
<x xml:space="preserve">Abstract</x> Tuning the ground states …︁ …︁ of bis(triphenylamine)benzedine bipolarons through substituent effects is described by X. Wang et al. in their Communication on page 2857 ff. The ground‐state structures of three bis(triphenylamine) dications, isolated by using weakly coordinating anions, were tunable through the donor substituents at the para positions of the triphenylamines. This gave rise to closed‐shell singlets and a new and stable diradicaloid structure motif with an excited triplet state in the solid state.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>